2021
DOI: 10.1007/s10654-020-00714-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of atrial fibrillation in the general population: meta-analysis of 23 cohort studies involving about 2 million participants

Abstract: Regular physical activity is well established to be associated with reduced risk of cardiovascular disease outcomes. Whether physical activity is associated with the future risk of atrial fibrillation (AF) remains a controversy. Using a systematic review and meta-analysis of published observational cohort studies in general populations with at least one-year of follow-up, we aimed to evaluate the association between regular physical activity and the risk of AF. Relevant studies were sought from inception until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…For comparisons that could not be transformed into extreme tertiles, the extreme groups (i.e. maximum versus minimal value of HGS) as provided by the reports were utilised for the analyses, as used in previous reports [36,42,44,45]. This methodology is considered reliable as shown in a previous review, which showed that pooled estimates from transformed and untransformed data are qualitatively similar [10].…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For comparisons that could not be transformed into extreme tertiles, the extreme groups (i.e. maximum versus minimal value of HGS) as provided by the reports were utilised for the analyses, as used in previous reports [36,42,44,45]. This methodology is considered reliable as shown in a previous review, which showed that pooled estimates from transformed and untransformed data are qualitatively similar [10].…”
Section: Meta-analysismentioning
confidence: 99%
“…The role of physical activity in improving health and reducing the risk of chronic disease outcomes such as vascular disease, diabetes and cancer is well known [42,44,48,56]. The beneficial effects of physical activity on these outcomes have been reported to be modulated through its beneficial effects on risk factors such as body weight, glucose, blood pressure, lipid profiles and inflammation [41].…”
Section: Introductionmentioning
confidence: 99%
“…Since the risk estimates could not be transformed into consistent comparisons, the extreme groups (i.e., top versus bottom or maximum versus the minimal amount of physical activity) reported for each study were used for the analyses. This approach, which we have utilised in previous similar meta-analyses [22][23][24][25], is considered reliable as it has been shown that pooled estimates from transformed and untransformed data are qualitatively similar [26]. When a study assessed specific types of physical activity in addition to total or any physical activity, we only used risk estimates for total or any physical activity in the pooled analysis.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…(30,31) However, to provide some consistency and enhance comparison and interpretation of the ndings, the extreme groups (i.e., the top versus bottom or maximum versus the minimal amount of physical activity) reported for each study were used for the analyses. Several previous meta-analyses have utilised this approach (12,13,32,33) and it is considered reliable as there is documented data that pooled estimates from transformed and untransformed data are qualitatively similar. (34) When a study reported speci c types of physical activity in addition to any or total physical activity, we only used risk estimates for any or total physical activity in the pooled analysis as done for previous similar reviews.…”
Section: Discussionmentioning
confidence: 99%